Social Entrepreneurship: A Pathway to Sustainable Development - Farooq, Khuram (Journal of Global Social Transformation, 2025)
Social entrepreneurship has been developed as a revolutionary method of solving social, environmental and economic problems through integrating business invention with a social impact mission. This model goes beyond conventional profit-driven entrepreneurship by offering the sustainable solutions that enhance the well-being of the community, inclusive development, and the contribution to the United Nations Sustainable Development Goals (SDGs). Social enterprises work across various industries such as education, health, environment, poverty eradication and livelihoods using new business models that provide financial sustainability and quantifiable social benefits. This academic paper discusses the role of social entrepreneurship as a medium to sustainable development through the analysis of its theoretical foundation, international and regional forms and effects of the concept on economic inclusion, social equity and environmental custodianship. The paper also presents enablers and barriers to development of social entrepreneurship based on empirical data of various nations and context-specific example. The results suggest that favorable policy environments, access to finance, capacity building, and a partnership of stakeholders are key success factors in improving the performance of social entrepreneurship towards the realization of sustainable development. Nevertheless, resource limitations, obstacles in regulation, and the limitations of scalability are the issues that need specific interventions. The paper ends by giving policy suggestions to policymakers, practitioners and scholars to enable an ecosystem that can utilize social entrepreneurship to achieve long-time sustainable development.
Keywords: social entrepreneurship; sustainable development; social innovation; impact measurement; inclusive growth; policy frameworks; SDGs